Virtual reality for the management of musculoskeletal pain: an umbrella review - Sultan Kalikanov; Aliya Baizhanova; Meiram Tungushpayev; Dmitriy Viderman; Dmitriy Viderman (Frontiers in Medicine)
BackgroundMusculoskeletal pain (MSK) is a condition that affects multiple parts of the musculoskeletal system, including limbs, neck, and back, leading to deterioration in both mental and physical health and overall quality of life. Despite the available treatments, they are not considered effective enough to eradicate pain symptoms, thereby requiring new methods as a substitute. This review comprehensively summarizes virtual reality (VR) technology as an adjunct or an alternative treatment for MSK pain and aims to explore the most suitable conditions and settings of VR.MethodsPubmed, Scopus, and Cochrane databases were searched for recent systematic reviews and meta-analyses investigating VR and MSK pain. The search was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and revealed 17 relevant articles. The AMSTAR-2 (A MeaSurement Tool to Assess systematic Reviews) analysis was conducted to assess the quality of included studies. The Corrected Covered Area was calculated to identify the degree of overlap.ResultsThe results found significant pain reduction and mental and physical improvements in patients with MSK pain in comparison to standard therapies in treating neck, knee, and back pain. Nevertheless, the heterogeneity and inconsistencies in results among papers were recognized. The promising aspects are multimodality, namely, VR in combination with exercises, patient acceptance of VR, and the effectiveness of immersive, non-immersive, and gamified versions. These findings also revealed the need for more research on underexplored regions, standardized methodologies, and personalized approaches.ConclusionTo summarize, VR poses the potential to treat MSK pain as an adjunct, and future research is recommended to focus on improving methodological rigor and multimodal approaches.Systematic review registrationOSF (https://osf.io/uyc7z).